Microbiological study and antimicrobial susceptibility pattern of ear infections in patients with Chronic Suppurative Otitis Media (CSOM) in Basrah Province - Reham M. Al-Mosawi (University of Thi-Qar Journal of Science, 2019)
The ear infections are highly popular disease in the world. Chronic suppurative otitis media (CSOM) is one of the prevalent hearing problems, this infection of the middle ear may extend to cranium that can cause many serious complications if not treated duly. It is famed for its return enduring infection.The causative agents of bacteria or fungi may be cause the CSOM infection. Therefore, our study is mainly aimed to identify the bacterial isolates which causing of CSOM and detect some isolates of fungi which implicated in this ear infection with performed of the antimicrobial susceptibility test.The study was executed on people whose attending the outpatients clinic of ENT in AL-Mwanee General Hospital during the period from November, 2016 to May, 2017 in Basrah governorate. Ear swab samples were collected and processed from eighty five (85) patients of CSOM by the following of standard bacteriological procedures mainly, for isolation and identification the bacterial pathogens, in addition, common diagnosis methods was used to detect of some fungal isolates.The positive microbial growth cultures were seen in 59 cases with frequent of (69.41 %) and 26 cases were negative in frequent of (30.58%). Their ages ranged from 1-60 years with high incidence of CSOM in age groups ≤ 10 and 31-50 years old in percent's of (38.82 % and  24.70 %) respectively. Polymicrobial samples from the total isolates (89) which identified in this study were (82) aerobic bacterial isolates in frequent (92.13 %) and 7 fungal isolates in frequent of (7.86 %).The most predominant bacterial isolated which causing CSOM was Pseudomonas aeruginosa in ratio (34.83 %) followed by Staphylococcus aureus, Streptococcus spp., Klebsiella pneumonia, Escherichia coli, Proteus mirabilis and P.vulgaris in proportions: 29.21% , 10.11% , 8.98% , 6.74% , 1.12% and 1.12% . While, the most common fungal detection which causing of CSOM was Aspergillus spp. and Candida spp. with frequently: 71.42% and 28.57%.Susceptibility test was done for known the best antibiotic agents which can be used as a proper treatment to CSOM infection. In the present study the most effective antibiotics agents for most of bacterial isolates were Ciprofloxacin, Vancomycin, Amikacin, Augmentin, Amox-Clav and Gentamycin.